2018
DOI: 10.4314/jae.v22i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Fish farmers’ attitude toward agricultural insurance scheme in Ondo State Nigeria

Abstract: The study assessed fish farmers' attitude towards agricultural insurance scheme (AIS) in Ondo State, Nigeria. A multi-stage sampling procedure was adopted to select the respondents for the study. Data were obtained through questionnaire and were analysed using descriptive statistics and mean score from a five point Likert type of scale. The study showed the mean age of fish farmers to be 44.6±10.1years and the majority (83.4%) were married. The mean household size was 5±2 and about 96% were able to read and wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…Each statement, had farmers indicating their level of agreement on a Likert scale. This is consistent with the data gathering approach for assessing attitudes towards agricultural insurance [42][43][44].…”
Section: Farmers' Risk Attitudes and Risk Management Coping Mechanismssupporting
confidence: 86%
“…Each statement, had farmers indicating their level of agreement on a Likert scale. This is consistent with the data gathering approach for assessing attitudes towards agricultural insurance [42][43][44].…”
Section: Farmers' Risk Attitudes and Risk Management Coping Mechanismssupporting
confidence: 86%
“…Most fish farmers in the study area who had not procured insurance had opted to be self-insured owing to the high costs of fish farming insurance and small-scale nature of their fish farming business. The findings are in agreement with Olayinka et al (2018), who, in their study in Ondo State, Nigeria, concluded that most fish farmers did not procure insurance due to the smallscale status of their fish farming business. Mohanty (2018) found adoption of aquaculture insurance as an adaptation strategy amongst shrimp farmers in India.…”
Section: Adaptation In Response To Extreme Climate Eventssupporting
confidence: 89%